Clonal types and antimicrobial resistance profiles of methicillin-resistant Staphylococcus aureus isolates from hospitals in south Brazil Tipos de clones e perfis de resistência antimicrobiana de Staphylococcus aureus resistentes à meticilina isolados de hospitais no sul do Brasil - Leandro Reus Rodrigues Perez; Pedro Alves D'azevedo (Revista do Instituto de Medicina Tropical de São Paulo, 2008)
In the present study were evaluated the DNA macrorestriction profile and SCCmec types for nine multi-resistant MRSA selected. Also antimicrobial susceptibility testing by disk diffusion method was evaluated for 68 MRSA isolates against 12 antimicrobial agents. The isolates were recovered from blood culture collected from hospitalized patients in three hospitals of Porto Alegre, Brazil. PFGE and PCR for mecA and SCCmec I, II, III, IV types genes were done on selected nine isolates with susceptibility only to vancomycin, teicoplanin and linezolid. Two clone profiles, with five subtypes, were demonstrated among multi-resistant MRSA analyzed. Eight isolates showed harbor SCCmec type III and one isolate was not typeable. The knowledge of SCCmec type, clone and antimicrobial profiles among S. aureus is essential mainly to prevention and control of dissemination of the antimicrobial resistance. No presente estudo foram avaliados o perfil de macrorrestrição do DNA e tipos de SCCmec para nove MRSA multirresistentes selecionados. Além disso, susceptibilidade a 12 agentes antimicrobianos pelo teste de disco-difusão foi avaliada para 68 isolados de MRSA. Os isolados foram obtidos de hemoculturas de pacientes hospitalizados de três hospitais de Porto Alegre, Brasil. PFGE e PCR para detecção do gene mecA e para os tipos genéticos SCCmec I, II, III e IV foram realizados em nove isolados selecionados que apresentaram susceptibilidade somente a vancomicina, teicoplanina e linezolida. Dois perfis clonais, com cinco subtipos, foram demonstrados entre os isolados analisados. Oito isolados apresentaram SCCmec tipo III e um isolado não foi caracterizado quanto ao tipo de SCCmec. O conhecimento do tipo de SCCmec bem como dos perfis clonais e de susceptibilidade aos antimicrobianos entre isolados de S. aureus é essencial, principalmente, para a prevenção e controle da disseminação da resistência antimicrobiana.